Modern problems of land management in context land protection - Novakovska, I. (Land Management, Cadastre and Land Monitoring, 2022)
In January of this year, the Government approved the Concept of the National Targeted Program for the Use and Protection of Land. Prerequisites have been created for the development and implementation of updated provisions on land management of rural areas, agricultural enterprises and households with the aim of organizing special protection of land as the main national wealth. The article presents an analysis of the main types of project-research works on land management that have been carried out since Ukraine gained independence. The special effect of anti-erosion and moisture-saving measures, which were achieved when the contour-ameliorative system of territory organization was introduced, was emphasized. The changes and features of land management with the cessation of quantitative and qualitative land accounting and the expansion of the composition of land management documentation at the expense of urban planning projects are considered. The structure of the land fund related to the implementation of the Concept of the Land Use and Protection Program and the development of land management documentation according to the stages of its implementation is characterized. The need to expand the constituent parts of land management schemes of territorial communities and to improve land monitoring. It was proposed to transfer the Institute of Soil Protection to the National Academy of Agrarian Sciences of Ukraine, and its main tasks were defined, In connection with the above Key words: land management, land use management, land protection, land relations, land monitoring, soil fertility.